Evaluation of University Library Websites of Sri Lanka - Silva, M.A.L. (My University, 2019)
The study created a framework consisted of 67 items to evaluate content and design features of university library websites of Sri Lanka by review of literature and expert evaluation. Besides, the paper evaluated the library websites of Sri Lanka based on the created framework and highlighted the points needed to be addressed in order to enhance the quality. Content richness of Sri Lankan library websites showed low levels of compliance (64.97%) to the framework than design features (82.57%). Among the Sri Lankan university library websites 21.43% have provided "Ask a librarian Service" and online help facility. None of the libraries have provided a glossary for library terminology and text alternatives (< alt> tags) for non-textual elements making websites inaccessible for differently able users. Present study highly recommended to redevelop the content of library websites of Sri Lanka by including all features described in the framework to provide better service to user community.
Keywords: Library website evaluation, Content of library websites, Design of library websites